Ferroelectricity in bis(ethylammonium) pentachlorobismuthate(iii): synthesis, structure, polar and spectroscopic properties. Issue 8 (15th June 2017) - Piecha-Bisiorek, Anna; Gągor, Anna; Jakubas, Ryszard; Ciżman, Agnieszka; Janicki, Rafał; Medycki, Wojciech
Abstract : A brief description of the thermal, structural and dielectric properties of bis(ethylammonium) pentachlorobismuthate(iii ) ferroelectric with P s that equals to 1.4 μC cm −2 at 180 K is presented. Abstract : A brief description of the thermal, structural and dielectric properties of bis(ethylammonium) pentachlorobismuthate(iii ) ferroelectric with P s that equals to 1.4 μC cm −2 at 180 K is presented. This paper focuses in particular on the molecular mechanism of a phase transition that is related mainly to the deformation of the anionic sublattice confirmed by temperature-variable powdered UV-Vis spectroscopy.